Oral Rehabilitation of patient with Cleft Lip and Palate- A Case Report - Vesna Ambarkova; Biljana Djipunova; Manu Batra; Slagana Trajkova (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Cleft lip and palate (CLP) is the most common congenital facial anomaly. About 70% of all the CLP cases and 50% of cleft palate only fall within non-syndromic pathologies. The purpose of this report was to show the clinical management of initial obturator therapy from birth to 3 months. The obturator was fabricated from the conventional orthodontic acrylic materials with cold polymerization (OrtoPoli, Polident, Slovenia). For successful treatment of cleft lip and palate patients, during the planning of prosthetic therapy one should take into consideration the deformation of maxillary segments\, as well as the disproportion between the upper and lower jaw alveolar ridge. Well planned prosthetic therapy will result in satisfactory function and aesthetics of a cleft palate patient.